A família Trago: uma ficção bem fundada - Fernandes, Margarida (Africana Studia, 2020)
Based on a fictional work, A família Trago, by the CapeVerdian wríter Germano Almeida, and taking the standpoint of Pierre Bourdieu, some issues relating to kinship, in the anthropological sense, are here discussed. We sustain that fiction writing should be considered as a valid source for anthropology.